Effect of tallow impregnation on moisture behavior and decay resistance of various wood species. Issue 4 (4th July 2021) - Sivrikaya, Hüseyin; Can, Ahmet; Yaman, Barbaros; Palanti, Sabrina; Morrell, Jeffrey J.
ABSTRACT: Beef tallow is a by-product of rendering of fats from meat production. While tallow can be used for a variety of applications including biodiesel production, it might also be useful for enhancing the water resistance of wood to improve durability. The effects of differing retentions of tallow on wood performance were evaluated in scots pine, beech and poplar. Tallow slowed but did not completely limit water uptake nor did it completely inhibit swelling. Fourier transform infrared spectroscopic analysis indicated that tallow did not appreciably alter the wood chemistry and TGA analysis suggested that it had only minor thermal effects. Fungal exposures suggested that tallow treatment improved decay resistance slightly but would not function as a stand-alone wood protectant. The results suggest that tallow might be a useful additive for bulking the wood to enhance water repellency of an existing preservative.